Analysis of endoscopic treatment of benign diseases of the biliary tract complicated by mechanical jaundice - Boyko, Valeriy; Yevtushenko, Denis; Avdosyev, Yuriy; Sochnieva, Anastasiia; Minukhin, Dmitriy; Shevchenko, Olexander (The Korean Association of Hepato-Biliary-Pancreatic Surgery, 2022)
Unsuccessful attempts at endoscopic papillo-sphincterotomy (EPST) with the need to further eliminate choledocholithiasis in another way, in our view, due to the lack of clear indications for the latter. This unresolved issue prompted us to look for alternative treatments for “endoscopically complex” forms of choledocholithiasis and to define clear criteria for their implementation. Aim. Analysis of ineffective attempts of endoscopic treatment of benign diseases of the biliary tract complicated by mechanical jaundice.
Keywords: endoscopic papillo-sphincterotomy; bleeding; endoscopic treatment; biliary tract treatment; mechanical jaundice